Altered perception and experience of “self” through the cultivation of bodily awareness : a phenomenological investigation among long-term body-based practitioners : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Cottrell-Davies, Siân (Massey University, 2023)
Extensive research points to the efficacy of “mindfulness” to alleviate diverse psychological and physical symptoms. However research has afforded markedly less attention to the lived experience and mechanisms of being mindful. This study investigated the perception and experience of “self” among long-term practitioners of body-based techniques, such as meditation, Yoga, Tai Chi Chuan, and forms of breathwork. Five participants were engaged in semi-structured interviews, with a single researcher adopting the Interpretative Phenomenological Analysis methodology. Four overarching themes emerged: “The corruption of thought-based perception”, “Contacting a more direct truth through embodiment”, “Beyond the obsession with the body: Contacting the true self or no-self?”, and “Self-reflection in the environment”. Theme two, relating to bodily awareness, was the dominant theme of the study, comprising four subcategories: “Experience lodged in the physiology”, “Living inside out”, “The relationship between thought and sensation”, and “Non-reactivity and release”. The current findings illuminate body awareness as a potent pathway to self-discovery, providing a more direct truth of one's place in the world and a gateway to a deeper self. By interweaving cognitive psychology, neurophenomenology, and both Eastern and Western philosophical systems, this study probes into simultaneous insight into an essential self as consciousness, and an absolute absence of self. All participants concurred that this process of self-discovery originated from an initial dedication to inward attention, anchoring on direct bodily sensations as opposed to the mind’s interpretations.
Keywords: 520406 Sensory processes, perception and performance